Comparative Analysis of Physical Activity, Time Management, and Self-Care Among Individuals with Type 2 Diabetes: A Multi-Population Cross-Sectional Study - Azarian, Somayeh; Siahkouhian, Marefat; Alves, Ana Sofia; Nobari, Hadi (International Journal of Sport Studies for Health, 2026)
Objective: The present study aims to examine the relationships among time management, physical activity, and self-care behaviors in individuals with T2DM, with a cross-population comparative method to better understand adherence challenges and inform culturally responsive strategies for diabetes care.Methods: This cross-sectional descriptive-analytical study examined the relationships between physical activity, time management, and self-care behaviors in adults with type 2 diabetes from Spanish and Iranian populations (n= 404, ). Validated questionnaires—IPAQ-SF, TMBS, and DSMQ—were used to assess physical activity Met, time use, and diabetes-related self-care, respectively, with all data collected ethically under approval code. Statistical analyses included MANOVA, Bonferroni-adjusted post hoc tests, and Pearson correlations to evaluate differences and associations across country, gender, and interaction effects.Results: Significant differences were found in physical activity and time management across gender, age, and cultural groups, with Spanish males demonstrating higher scores. No group-level differences were observed in self-care behaviors. Time management was positively correlated with both physical activity and self-care in both populations.Conclusion: This comparative study highlights time management as a key behavioral determinant of self-care in individuals with type 2 diabetes, surpassing physical activity in predictive strength across Spanish and Iranian cohorts. Findings underscore the need for culturally tailored, time-focused interventions that support sustainable self-management, particularly among older adults and women. Culturally tailored strategies—such as Iran’s localized health instruction initiatives and Spain’s region-specific dietary counseling rooted in Mediterranean traditions—play a fundamental role in enhancing diabetes self-management. By connecting clinical objectives with cultural recognition and personal relevance, these suggestions foster greater patient engagement, behavioral adherence, and long-term health improvement.